Architecture and freedom : searching for agency in a changing world. - Hopkins, Owen, 1984- (Architectural design (London, England : 1971), 2018)
The issue is split into four sections. Featuring contributions by prominent architects Reinier de Graaf of OMA and Alejandro Aravena of Elemental, the first section focuses on the values that shape the practice of architecture, and the relevance, or otherwise, of moral principles or ethical codes and standards.